ANALYSIS OF ASSESSMENT OF CHILD-FRIENDLY SCHOOL POLICY AT THE ESTABLISHMENT AND DEVELOPMENT STAGE - Lutfa, Asna (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2022)
Determination of Child Friendly Schools (SRA) is organized through two stages. They are the preparation and planning stages and the establishment and development stages. Based on the Child Friendly School Guidelines, at the establishment and development stage, six components were verified, one of them was the SRA policy component. According to the author, the process of determining the SRA is dynamic, so it is not enough if only the verification process is carried out. In order for the assessment of the components of the SRA policy at the establishment and development stage to obtain accountable results, the assessment must be based on values. Assessment methods that can be carried out include verification methods, analytical rubric measurements, surveys, written tests, written essays, oral questions and answers, oral or written comments, homework, self/peer assessment methods, portfolios, simulations, demonstrations, and observation method.